Research into the possibility of producing ferrosilicoaluminum from recycled materials - Taran , O.Yu.; Ovcharuk , A.M.; Malyi , E.D. (Theory and Practice of Metallurgy, 2025)
The technology of electrothermal production of ferrosilicoaluminum using recyclable material from abrasive production has been developed, studied and tested in laboratory and semi-industrial conditions. The following were used as burden components: "old charge" from silicon carbide production, sludge from abrasive electrocorundum and silicon carbide, magnetic fraction from electrocorundum production and gas coal. As a result, an alloy containing 61−69% Al+Si was obtained.